FPSO (Floating Production Storage and Offloading) Motion Analysis using Mooring Radius Variations Based on Time Domain Simulation (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Along with the development of technology, oil and gas exploration has begun to be carried out in the deep sea. One technology that can be used is FPSO (Floating Production Storage and Offloading). In order for the FPSO to be damped due to environmental loads during the production process, a mooring system is needed that meets standards according to the needs and environmental characteristics of the oil field. The mooring system used is a spread mooring system which is limited to 12 mooring lines. The research uses variations in the mooring line radius so that the length of the mooring line and the anchor position are different. This research is intended to analyze the effect of the mooring line radius on FPSO movement and the tension of the mooring line itself using a numerical approach with ANSYS AQWA software. From this study it can be seen that by increasing the length of the mooring line there will be a reduction in maximum tension on the mooring line, but the opposite is true there is an additional offset to the ship's movement. However, because the anchor position is further away in each radius, the tension value on the mooring line does not have a significant difference
Keywords: Tension; Mooring line; FPSO